Fast-growing willows significantly reduce invasive knotweed spread. (1st February 2019) - Dommanget, Fanny; Evette, André; Breton, Vincent; Daumergue, Nathan; Forestier, Olivier; Poupart, Philippe; Martin, François-Marie; Navas, Marie-Laure
Abstract: Competitive interactions seem to play a major role in invasive plant success. However, they have mostly been addressed through the invader impacts on other species of the plant community and rarely through the way plant communities can contain alien species. Understanding such mechanisms would help in designing restoration projects using plant community competitive properties to control invasive populations. In this study, we looked at the role of competitive interactions in the success of Fallopia japonica (Houtt.) Ronse Decraene using a native willow frequently used in bioengineering techniques: Salix viminalis L. S. viminalis has a high growth rate and is, as such, a potential candidate to compete with F. japonica in restoration projects of invaded areas. Both species were grown in semi-controlled conditions in mesocosms (truck dumpsters), alone or in competition. Morphological traits (plant height, specific leaf area) as well as biomass (aboveground and underground) were measured on each species during two growing seasons. We also quantified spatial expansion of F. japonica . Even under a dense canopy of S. viminalis, F. japonica was able to survive and grow. However, its performance was significantly reduced compared to monocultures and its spatial colonization was less extended. Although S. viminalis biomass was affected by F. japonica, F. japonica expressed competitive stress through a modification of ramet density and height. There was no significant effect of F. japonica on S. viminalis height, enabling this species to dominate. Synthesis and applications: We conclude that S. viminalis succeeded in reducing F. japonica growth by developing a competitive canopy. Bioengineering techniques aiming at restoring a competitive neighborhood can control F. japonica . However, F. japonica 's broad underground extension should be taken into account in any management strategy in order to successfully limit its development and spatial spread. Graphical abstract: Image 1 Highlights: Fallopia japonica survived and spread despite a dense Salix viminalis cover. The performance of F. japonica was reduced under high interspecific competition. Salix viminalis was less affected by interspecific competition than F. japonica. F. japonica affected S. viminalis more broadly underground than aboveground. S. viminalis is a good candidate to contain F. japonica in ecosystem restoration.